Recreational angling tournaments: Participants' expenditures - John A. Curtis; Benjamin Breen; Paul O'Reilly (The Economic and Social Research Institute (ESRI), 2016)
Fishing tournaments are a common feature in recreational angling across a wide range of target species both in fresh and salt waters. Tournaments are organised for a number of purposes, including as commercial enterprises; as fund-raising initiatives for angling clubs; for economic development purposes (e.g. tourism); as well as improve participants' skill levels. Most tournaments are confined to geographically small areas and usually occur over a small number of days, which can mean a pulse of economically significant activity in the local area. This paper analyses the nature of expenditure associated with angling tournaments, including travel, food and accommodation, and angling-related expenditures as a function of socio-economic and angler characteristics. Analysis based on 106 tournaments across Ireland during 2013 finds a clear 80/20 segmentation between "high" and "low" spend anglers and that the segmentation occurs across all fish target species considered. The analysis also finds that British coarse anglers participating at Irish angling tournaments spend considerably more than other anglers irrespective of target species or angler country of origin.
Keywords: 330